The Link between Economic Growth and Ecological Footprint: What Future Prospects for the G7 Countries: PMG-ARDL - Dardouri, Nesrine; Smida, Mounir (Migration Letters, 2023)
Given the need to achieve economic development while preserving environmental quality, our main objective in this article is to study the impact of economic growth on the ecological footprint in the G7 countries (Italy, France, Canada, the United States, United Kingdom, Japan, Germany) over the period 1961-2018. By studying the environmental Kuznets curve (EKC) using the dynamic ARDL panel, we found that the relationship between EFP (ecological footprint) and GDP is N-shaped. In the renewable Kuznets curve (RKC), we found a U-shaped relationship. The international investment position and debt then contribute to pollution, and the consumption of renewable energy reduces CO2 emissions. However, additional efforts are needed to promote renewable energy in the countries analyzed.